(untitled) (Global Journal of Science Frontier Research, 2011)
The aim of this paper is to establish sufficient conditions for the function z pÏˆq (z) to be in the classes of uniformly starlike and uniformly convex functions associated with the parabolic region Re Ï‰ > | âˆ’ 1 Ï‰ | . Further, convolution of the functions which are analytic in the open unit disk with negative coefficients have been investigated. Finally, similar results using an integral operator have also been obtained.